Systematics of Cauquenia (Araneae : Zoropsidae), with comments on the patterns of evolution of cribellum and male tibial crack on Lycosoidea - Piacentini, Luis Norberto (2013)
A new genus of the spider family Zoropsidae, Cauquenia, gen. nov., is proposed for Cauquenia maule, sp. nov., from the Maule region in central Chile. The familial placement is tested through the inclusion of Cauquenia in the latest major published morphological analyses of the superfamily Lycosoidea, and the subfamily placement of the South American zoropsid genus Itatiaya Mello-Leitão is also tested including them in the Raven and Stumkat (2005) analysis. Cauquenia and Itatiaya are closely related to the African genera Griswoldia Dippenaar-Schoeman & Jocqué and Phanotea Simon, with which it shares a cup-shaped median apophysis on the male pedipalp and tooth-like projections on the lateral lobes of the epigyne in females. The patterns of evolution of the cribellum and the male tibial crack in Lycosoidea are explored; the cribellum shows up as primitively present, with three losses and four independent acquisitions, and the male tibial crack is lost twice. An asymmetric cost in cribellum gain : loss of 6 : 1 produces a primitive cribellum with 12 losses.